Does economic growth deliver jobs? Revisiting Okun's Law - Sangheon Lee; Dorothea Schmidt-Klau; Johannes Weiss; Juan Chacaltana (International Labour Organization (ILO), 2020)
This paper revisits the relationship between economic growth and employment creation as expressed in Okun's law by using the latest updated global ILO dataset for new and more detailed estimates. The analysis confirms that there are important variations across regions of the world and income levels in both magnitude and significance of this relationship: In developing and emerging countries, the Okun's coefficient is lower than in developed countries. Moreover, there are important differences depending on the labour market structures as given by the level of informality or the relative presence of SMEs in the labour markets. Furthermore, the paper examines the extent to which the sectoral composition of growth is associated with the responsiveness of unemployment to business cycles: In developed economies, there are large variations in sectoral elasticities while in developing and emerging countries, the role of sectoral composition is limited. While further research is needed to better understand the relationship between economic growth and employment, especially in the presence of high informality (and SMEs), the analysis in this paper calls for greater caution in using Okun's coefficients to inform policy decisions.
Keywords: 330; employment; economic growth